Risk Sharing Within and Outside the Firm: The Disparate Effects of Wrongful Discharge Laws on Expected Stock Returns - Robert Mahlstedt; Rüdiger Weber (Institute of Labor Economics (IZA), 2020)
We study the effect of wrongful-discharge laws (WDL) on firm-level stock returns. We find disparate effects depending on the exact design of the law. Consistent with rational, risk-based pricing, the effect on returns seems to be linked to how firms share systematic risk with their employees under the respective laws. Firms in states with WDLs prohibiting employers from acting in bad faith have more intra-firm risk sharing and lower expected returns. Vaguer legislation that prohibits discharges in retaliation for acting in accordance with public policy is associated with less intra-firm risk sharing and higher expected returns.
Keywords: G12; J38; G38; 330; labor protection; expected stock returns; risk sharing